Morphological, Ultrastructural, Motility and Evolutionary Characterization of Two New Hemistasiidae Species - Prokopchuk, Galina; Tashyreva, Daria; Yabuki, Akinori; Horák, Aleš; Masařová, Petra; Lukeš, Julius (Protist, 2019)
Until now, Hemistasia phaeocysticola was the only representative of the monogeneric family Hemistasiidae available in culture. Here we describe two new axenized hemistasiids isolated from Tokyo Bay, Japan. Like in other diplonemids, cellular organization of these heterotrophic protists is characterized by a distinct apical papilla, a tubular cytopharynx contiguous with a deep flagellar pocket, and a highly branched mitochondrion with lamellar cristae. Both hemistasiids also bear a prominent digestive vacuole, peripheral lacunae, and paraflagellar rods, are highly motile and exhibit diverse morphologies in culture. We argue that significant differences in molecular phylogenetics and ultrastructure between these new species and H. phaeocysticola are on the generic level. Therefore, we have established two new genera within Hemistasiidae - Artemidia gen. n. and Namystynia gen. n. to accommodate Artemidia motanka, sp. n. and Namystynia karyoxenos, sp. n., respectively. A. motanka permanently carries tubular extrusomes, while in N. karyoxenos, they are present only in starving cells. An additional remarkable feature of the latter species is the presence, in both the cytoplasm and the nucleus, of the endosymbiotic rickettsiid Candidatus Sneabacter namystus.
Keywords: zátoky; Movement; fylogeneze; pohyb; Phylogeny; Eukaryota; Bays; Japan; Japonsko